The evolution of "Technological and Economic Development of Economy“: a bibliometric analysis - Yu, Dejian; Xu, Zeshui; Šaparauskas, Jonas (Technological and Economic Development of Economy, 2019)
The Technological and Economic Development of Economy (TEDE) journal was founded 25 years ago and it plays an important role in the economic field. The purposes of this study are to present a bibliometric analysis of the TEDE publications that are included in the Social Science Citation Index (SSCI) database and identify the characteristics and evolution of the TEDE journal through some commonly used as well as various kinds of newly designed indicators. Firstly, annual and geographical distributions, author and manuscript characteristics of the TEDE publications are explored. Secondly, leading contributors including countries/territories, institutions, and authors are presented. The thematic analyses based on co-occurrence of keywords are presented lastly. The main advantages of this study are that all the analysis results are entirely based on objective data and the complex and important results are visualized. This study helps in understanding the development of the TEDE journal and has certain reference value for scholars in the economic field.